Аналіз іннноваційної активності вітчизняних підприємств - Шейко, І. А. (ХНУРЭ, 2015)
Iindicators of innovation activity in Ukraine, Kharkov region were analyzed: level of innovation activity, the sum of unding of innovation activity. The structure of funding sources for innovation activity was analysed. Also factors that can influence the level of innovation activity – foreign direct investments, sum of investments,the indices of industrial products for Ukrainian industry, machinery industry and Kharkov region were described.
Keywords: іннноваційна активність підприємства; іннноваційна активність